. - Kothari, Rajni (Bombay, 1976)
This little book deals with the present crisis in our polity and the con comitant crises in our economic performance, the functioning of our administration, our educational system, and a variety of other policy spheres. It seeks to deal with these issues in a comprehensive framework, provides a diagnosis of the current situation, and outlines in some detail the constituents of an alternative model. Its analysis is based on the conviction that not only has our performance as a democratic polity sharply declined in various spheres in the past decade or so but that underlying this decline are some inherent faults in our system which have now come to surface. It is therefore neces sary to think of an alternative model for ourselves, building no doubt on the positive features of our system and explicitly recognizing the values that we adopted at the start of our career as an independent polity, but at the same time purging the system of the consequences of its past mistakes and enabling it to deal with new challenges and magnitudes that are now emerging on the horizon. A major crisis - what India faces is no minor crisis is also an occasion for basic rethinking and an opportunity for reconstruction. It is necessary that both intellectuals and political leaders engage in such a task. The pages that follow address themselves to it.
Keywords: Social change